A feasibility study to assess non-clinical community health workers' capacity to use simplified protocols and tools to treat severe acute malnutrition in Niger state Nigeria - Olatunde Adesoro; Olusola Oresanya; Helen Counihan; Prudence Hamade; Dare Eguavon; Chika Emebo; Bethany Marron; Naoko Kozuki; Amina Isah; Patrick Gimba; Chris Osa Isokpunwu; Kolawole Maxwell; et al. (BMC, 2021)
Abstract Background Severe acute malnutrition (SAM) is a major determinant of childhood mortality and morbidity. Although integrated community case management (iCCM) of childhood illnesses is a strategy for increasing access to life-saving treatment, malnutrition is not properly addressed in the guidelines. This study aimed to determine whether non-clinical Community Health Workers (called Community-Oriented Resource Persons, CORPs) implementing iCCM could use simplified tools to treat uncomplicated SAM. Methods The study used a sequential multi-method design and was conducted between July 2017 and May 2018. Sixty CORPs already providing iCCM services were trained and deployed in their communities with the target of enrolling 290 SAM cases. Competency of CORPs to treat and the treatment outcomes of enrolled children were documented. SAM cases with MUAC of 9 cm to < 11.5 cm without medical complications were treated for up to 12 weeks. Full recovery was at MUAC≥12.5 cm for two consecutive weeks. Supervision and quantitative data capturing were done weekly while qualitative data were collected after the intervention. Results CORPs scored 93.1% on first assessment and increment of 0.11 (95% CI, 0.05-0.18) points per additional supervision conducted. The cure rate from SAM to full recovery, excluding referrals from the denominator in line with the standard for reporting SAM recovery rates, was 73.5% and the median length of treatment was 7 weeks. SAM cases enrolled at 9 cm to < 10.25 cm MUAC had 31% less likelihood of recovery compared to those enrolled at 10.25 cm to < 11.5 cm. CORPs were not burdened by the integration of SAM into iCCM and felt motivated by children's recovery. Operational challenges like bad terrains for supervision, supply chain management and referrals were reported by supervisors, while Government funding was identified as key for sustainability. Conclusion The study demonstrated that with training and supportive supervision, CORPs in Nigeria can treat SAM among under-fives, and refer complicated cases using simplified protocols as part of an iCCM programme. This approach seemed acceptable to all stakeholders, however, the effect of the extra workload of integrating SAM into iCCM on the quality of care provided by the CORPs should be assessed further.